(untitled) (Journal Of Educational and Psychological Researches, 2017)
It aim current researchs֬ to identify the impact of a proposed strategy in accordance with the objectives of science in the achievement and some science processes, where the experimental method was adopted, and define the research community was students second grade averag in Education Bagdad / Rusafa third, research sample intentionally chosen as school Radwan, and (30) students experimental group and (29) of control group, research tools were achievement test and the test of science operations and use the appropriate statistical tools to process information and data, showing results, the experimental group surpassed the control group in the collection and operations science, and light it, the researcher recommended several recommendations